2017
DOI: 10.1139/gen-2016-0097
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis and expression characteristics of small auxin-up RNA (SAUR) genes in moso bamboo (Phyllostachys edulis)

Abstract: Moso bamboo (Phyllostachys edulis) is well known for its rapid shoot growth. Auxin exerts pleiotropic effects on plant growth. The small auxin-up RNA (SAUR) genes are early auxin-responsive genes involved in plant growth. In total, 38 SAUR genes were identified in P. edulis (PheSAUR). A comprehensive overview of the PheSAUR gene family is presented, including the gene structures, phylogeny, and subcellular location predictions. A transcriptome analysis indicated that 37 (except PheSAUR18) of the PheSAUR genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Among the early auxin response genes, the SAUR gene family has the largest number of member; it is estimated that around half of the Arabidopsis SAUR gene transcripts are rapidly upregulated by auxin, while a small number of this family members appear to be repressed by auxin [ 60 , 61 ]. Recently, a genome-wide analysis of SAUR genes was performed in moso bamboo [ 62 ]. Of the 38 SAUR genes identified, 10 SAUR genes changed their expressions under our auxin treatment conditions, the expression levels of 7 of those genes increased, whereas 3 genes decreased (Additional file 12 : Table S17).…”
Section: Resultsmentioning
confidence: 99%
“…Among the early auxin response genes, the SAUR gene family has the largest number of member; it is estimated that around half of the Arabidopsis SAUR gene transcripts are rapidly upregulated by auxin, while a small number of this family members appear to be repressed by auxin [ 60 , 61 ]. Recently, a genome-wide analysis of SAUR genes was performed in moso bamboo [ 62 ]. Of the 38 SAUR genes identified, 10 SAUR genes changed their expressions under our auxin treatment conditions, the expression levels of 7 of those genes increased, whereas 3 genes decreased (Additional file 12 : Table S17).…”
Section: Resultsmentioning
confidence: 99%
“…Their high abundance may be essential for auxin polar transport and cell division during bamboo shoot growth. Many studies have demonstrated that SAUR proteins can promote cell elongation (Bai et al ., ; Li et al ., ). In the early growth period, SAUR gene families were lowly expressed, but as cell elongation replaced cell division in shoot growth, SAUR family expression increased.…”
Section: Discussionmentioning
confidence: 99%
“…An auxin early response gene, SAUR , can be transcriptionally induced by auxin within minutes without the need for de novo synthesis of the protein. The research on the biological functions of SAUR mainly focuses on hypocotyl growth, stem elongation, and auxin transport [ 42 ]. Spartz et al found that SAUR019 activates plasma membrane H + -ATPases by inhibiting PP2C-D phosphatases to promote cell expansion, which provides evidence for the acid growth theory.…”
Section: Discussionmentioning
confidence: 99%